Proceedings the 2nd conference on food science & technology : (Cantho University, 2013)
Contents: Food engineering at Massey University, Analysis and applications of milk fat globule membrane material, Sunflower oil supplemented with Schizophyllum commune extract: Its oxidative stability during accelerated storage,...